2023
DOI: 10.3389/fimmu.2023.1137659
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast heterogeneity: Keystone of tissue homeostasis and pathology in inflammation and ageing

Abstract: Fibroblasts, derived from the embryonic mesenchyme, are a diverse array of cells with roles in development, homeostasis, repair, and disease across tissues. In doing so, fibroblasts maintain micro-environmental homeostasis and create tissue niches by producing a complex extracellular matrix (ECM) including various structural proteins. Although long considered phenotypically homogenous and functionally identical, the emergence of novel technologies such as single cell transcriptomics has allowed the identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 170 publications
0
9
0
Order By: Relevance
“…Their cytokine production can influence the balance between pro-fibrotic and anti-fibrotic mechanisms in irradiated tissues ( 112 ). For example, a study has suggested that B cells can affect the fibrotic process by altering the cytokine milieu, impacting the activation and function of fibroblasts and immune cells ( 113 ). This role of B cells in fibrosis highlights the complexity of the immune response in radiation-induced skin damage and underscores the need for a comprehensive understanding of the adaptive immune responses in the development of effective treatments for fibrosis.…”
Section: Molecular Mechanisms Of Fibrosismentioning
confidence: 99%
“…Their cytokine production can influence the balance between pro-fibrotic and anti-fibrotic mechanisms in irradiated tissues ( 112 ). For example, a study has suggested that B cells can affect the fibrotic process by altering the cytokine milieu, impacting the activation and function of fibroblasts and immune cells ( 113 ). This role of B cells in fibrosis highlights the complexity of the immune response in radiation-induced skin damage and underscores the need for a comprehensive understanding of the adaptive immune responses in the development of effective treatments for fibrosis.…”
Section: Molecular Mechanisms Of Fibrosismentioning
confidence: 99%
“…Notably, single‐cell RNA‐sequencing studies of oral mucosal tissues have demonstrated differences in the transcriptomic profile of fibroblast populations, a subset of which was enriched with chemotactic signatures including CXCL1 and CCL2 (Ko et al., 2023; Williams et al., 2021). While these studies highlight the underappreciated role of endogenous fibroblasts in immune modulation for maintaining homeostasis or in facilitating disease progression (S. Davidson et al., 2021; Gauthier et al., 2023), investigating specific inflammatory fibroblast subset has been difficult due to the lack of available in vivo mouse models.…”
Section: Introductionmentioning
confidence: 99%
“…Under different pathological conditions, such as wound healing, malignancy, or other inflammatory disorders, normal fibroblasts can be activated and secrete cytokines to interact with other cells. Fibroblasts and other types of cells in the cutaneous EIME, such as epithelial cells, endothelial cells, pericytes, and adipocytes, can develop into myofibroblasts, or cancer-associated fibroblasts (CAFs) which are a heterogenous population of activated fibroblasts playing key roles in tumor microenvironment and affecting tumor proliferation, metastasis, and chemotherapy resistance ( Figure 1 ) ( 19 , 20 ). The activation states of fibroblasts are closely involved in the pathogenesis of diverse inflammatory skin diseases.…”
Section: Introductionmentioning
confidence: 99%